FUNCTIONS AND OBJECTIVES OF TREASURY SOME FOREIGN COUNTRIES - Гаврилішин, А. П.; Козирєва, В. П. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
This article deals with topical issues and systematize historical experience and activities of the Treasury on the example of some foreign countries.